Pemberian Aromaterapi Jahe terhadap Pasien Gangguan Pemenuhan Nutrisi dengan Mual Muntah Post Apendektomi - Yassirli Amrina; Ida Nurjayanti (Universitas Muhammadiyah Manado, 2023)
Background: During the appendectomy procedure the patient will receive anesthesia which has several side effects, one of which is postoperative nausea and vomiting (PONV). Nonpharmacological therapy that nurses can do to reduce postoperative nausea and vomiting is with ginger aromatherapy. .Purpose: This case study aims to determine the effectiveness of giving ginger aromatherapy to nausea and vomiting in patients with post-appendectomy. Methods: The method used in writing is a case report with ginger aromatherapy intervention carried out for 3 days. Results: The results of this case study showed that after 3 days of ginger aromatherapy intervention, there was a decrease in the RINVR score from 15 (moderate nausea and vomiting) to 2 (mild nausea and vomiting). Conclusion: Ginger aromatherapy is effective in reducing nausea and vomiting in post-appendectomy patients.